Regularity criterion for the 3D Hall-magnetohydrodynamic equations involving the vorticity. (October 2016) - Ye, Zhuan
Abstract: In this paper we study the three-dimensional (3D) incompressible Hall-magnetohydrodynamic (Hall-MHD) equations and obtain its regularity criterion only in terms of the vorticity field. As a consequence, it improves the known results.